Implementasi Penerimaan Peserta Didik Baru untuk Pemenuhan Hak Konstitusional dalam Bidang Pendidikan di Kota Surakarta - Dewangga Bangun; Achmad Achmad (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2021)
ABSTRACTThis study analyze the implementation of student enrollment with zoning system in Junior and Senior High School towards fullfilment of constitutional rights in education and the obstacles faced in the implementation. This research is empirical legal research and is descriptive in nature. This study uses qualitative approach with sources of legal material in the form of primary and secondary legal materials. The legal material collection techniques used were interviews and literature studies. Both student enrollment based on Ministerial of Education and Culture Regulation Number 20 of 2019. Technically, set with Mayor of Surakarta Regulation Number 17 of 2019 and Governor of Central Java Regulation Number 22 of 2019. Junior High School prioritize student from nearest zone radius with minimum quota of 85% while Senior High School prioritize student from nearest zone with minimum quota of 80%. The fullfilment of constitutional rights in education in Junior High School Enrollment running relatively optimal with one of the indicators, by being able to absord all of the registrants, while Senior High School can not accommodate many of the registrants. There are several obstacles faced in 2019’s enrollent, it’s as varied as the unequity school distribution, insufficient schools capacity, sudden policy change, inefficient registration process, area expantion, registrant with “Other Family” status had trouble in registering, and difficult determining the achievement components.Keywords : student enrollment; zoning system; constitutional rights.